Mosque is the only visible shelter at the most dangerous time: a qualitative study of the victims’ experience in the MT semeru eruption - Sriyono; Zulkarnain, Hakim; Proboningsih, Jujuk; Mufarika, Mufarika; Akbar, Dian Rahmadin (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the evacuation behaviour of victims during acute natural disaster. Method: The qualitative, phenomenological study was conducted in Lumajang Regency, Indonesia, from December 5 to 12, 2021, and comprised disaster victims who had just been evacuated from the Mount Semeru eruption disaster site. Data was collected using a semi-structured interviews and observations. Data was analysed using Colaizzi’s qualitative method. Results: There were 18 subjects aged 19-60 years. They were interviewed in two groups, with the first group having 11(61.1%) subjects and the other 7(38.9%). On the basis of the data collected, 4 themes emerged. The first theme was emphasis on ‘evacuation together’. The second theme was ‘helping others in need’. The third theme was ‘local wisdom passed down through generations’. The fourth theme was ‘mosque being the only bright site’ which made it the destination of choice for evacuation. Conclusion: Disaster victims remember well the buildings they frequent. This is a good solution for determining shelter points during a disaster. There needs to be a regulation and preparation at the evacuation referral point so that victims may survive during acute disasters. Keywords: Disaster, Eruption, Evacuation, Religious belief, Mass psychology.